A impossibilidade da efetivação dos direitos fundamentais nos estados antidemocráticos através da concepção Salgadiana de justiça - Micaela Afonso Lamounier (2019)
The present dissertation proposes to analyze the reasons why it is not possible to enforce fundamental rights in anti-democratic states and, consequently, inconceivable becomes the realization of justice in the way that is set by the master and also theoretical framework of this work, Joaquim Carlos Salgado. Therefore, given the social value of fundamental rights and the use of the philosophy and idea of justice developed by Salgado, it seeks to approximate the realization of fundamental rights with democracy, in such a way that the present study will investigate why, without the communion of both, the achievement of justice in the contemporary world is not possible. Thus, there is in the Democratic State of Law the difficulty regarding the enforcement of basic rights provided for in the Constitutions, however, this challenge is not comparable to the obstacle existing in despotic countries, taking into account that, in such situations, it is not possible to demand the enforcement of these rights. In this sense, the work Salgadiana explains that first there is the awakening of popular awareness about the existence of a collection of fundamental rights applicable to every human being, so that after they are positivized in the legal order and, ultimately, the enjoyment by every subject of universal law. Certainly, without the realization of the multiplied rights, today's justice is not possible, since, according to the author above, contemporary justice is realized through the maximum ethical, where the fundamental rights are foreseen and realized in the Democratic State of Law. Thus, the purpose of this research is to contribute in order to bring to the light of the debate the conception that despotic nations do not offer to their social body the effectiveness of subjective rights considered fundamental.